VD_FINDINFO HC / 2019 / 835 vom 9. September 2019 - VD Tribunal cantonal (2019)
PRESCRIPTION, RENONCIATIONSENS GÉNÉRAL, ACTION EN DOMMAGES-INTÉRÊTSEN GÉNÉRAL, CONNAISSANCE, DÉCISION INCIDENTE | 60 al. 1 CO, 237 CPC (CH)